2014
DOI: 10.1093/icvts/ivu143
|View full text |Cite
|
Sign up to set email alerts
|

A personalized approach to interventional treatment of tricuspid regurgitation: experiences from an acute animal study

Abstract: We demonstrated the feasibility in principle of a personalized interventional treatment for tricuspid regurgitation using a braided stent, based on individual cardiac imaging, with anchoring forces mainly exerted on the venae cavae and on the inner surface of the right atrium. The design process of this device is a good indicator of the growing potential of an imaging-based personalized simulation and production approach for the treatment of tricuspid valve disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Beyond a surgical guide for hard tissue ( 30 ), a surgical guide with flexible material could be used in partial carcinectomy of soft organs. Regarding implantable devices, a recent study showed that 3DP-based personalized stents could be used for tricuspid regurgitation ( 51 ). In addition, a patient-specific flexible implant for filling a dead zone in the lung after pneumonectomy with a nonmedical-grade silicon material was developed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond a surgical guide for hard tissue ( 30 ), a surgical guide with flexible material could be used in partial carcinectomy of soft organs. Regarding implantable devices, a recent study showed that 3DP-based personalized stents could be used for tricuspid regurgitation ( 51 ). In addition, a patient-specific flexible implant for filling a dead zone in the lung after pneumonectomy with a nonmedical-grade silicon material was developed.…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem autopsy (H, I) and CT fluoroscopy (J) revealed accurate positioning of valve prostheses. Adapted from Amerini et al Interact Cardiovasc Thorac Surg 2014;19:414-418, with permission of Oxford University Press ( 51 ).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…gave an overview about some novel percutaneous approaches for the tricuspid valve implantation found in literature . Some devices designed for the orthotopic position reached the state of in vivo animal trials . Lauten et al.…”
mentioning
confidence: 99%
“…Pott et al gave an overview about some novel percutaneous approaches for the tricuspid valve implantation found in literature (9). Some devices designed for the orthotopic position reached the state of in vivo animal trials (10)(11)(12)(13). Lauten et al reported two cases of patients who were treated with their device in heterotopic position inside the inferior vena cava (IVC) (14) and inside the inferior and superior vena cava (SVC) (15).…”
mentioning
confidence: 99%